Genome-Wide Association Analysis Identifies a Genetic Basis of Infectivity in a Model Bacterial Pathogen. (13th July 2020) - Andras, Jason P; Fields, Peter D; Du Pasquier, Louis; Fredericksen, Maridel; Ebert, Dieter
Abstract: Knowledge of the genetic architecture of pathogen infectivity and host resistance is essential for a mechanistic understanding of coevolutionary processes, yet the genetic basis of these interacting traits remains unknown for most host–pathogen systems. We used a comparative genomic approach to explore the genetic basis of infectivity in Pasteuria ramosa, a Gram-positive bacterial pathogen of planktonic crustaceans that has been established as a model for studies of Red Queen host–pathogen coevolution. We sequenced the genomes of a geographically, phenotypically, and genetically diverse collection of P. ramosa strains and performed a genome-wide association study to identify genetic correlates of infection phenotype. We found multiple polymorphisms within a single gene, Pcl7, that correlate perfectly with one common and widespread infection phenotype. We then confirmed this perfect association via Sanger sequencing in a large and diverse sample set of P. ramosa clones. Pcl7 codes for a collagen-like protein, a class of adhesion proteins known or suspected to be involved in the infection mechanisms of a number of important bacterial pathogens. Consistent with expectations under Red Queen coevolution, sequence variation of Pcl7 shows evidence of balancing selection, including extraordinarily high diversity and absence of geographic structure. Based on structural homology with a collagen-like protein of Bacillus anthracis, we propose a hypothesis for the structure of Pcl7 and the physical location of the phenotype-associated polymorphisms. Our results offer strong evidence for a gene governing infectivity and provide a molecular basis for further study of Red Queen dynamics in this model host–pathogen system.